FACTORS AFFECTING INTENTION TO USE NATIONAL SINGLE WINDOW (NSW) THROUGH PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS IN IMPORT, EXPORT AND LOGISTICS ENTERPRISES - Sriboonlue, Orawee (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – The purposes of this research were to study factors affecting intention to use National Single Window (NSW) through perceived ease of use and perceived usefulness in import, export, and logistics enterprises. Methodology – The research methodology was quantitative research with survey method by using questionnaires for data collection. The respondents were 400 participants, who are importers, exporters, and logistics service providers which are located in the Bangkok Metropolitan Region. Descriptive statistics used for data analysis included frequency, percentage, mean, and standard deviation. Due to hypothesis testing, inferential statistics were used, specifically Pearson’s Product Moment Correlation Coefficient and Partial Least Squares-Structural Equation Modeling (PLS-SEM). Results – The results of hypothesis testing revealed that acceptance and use of technology had a positive and significant effect on perceived ease of use and perceived usefulness whereas organizational support had a positive and significant effect on perceived ease of use, and technology experience had a positive and significant effect on perceived ease of use and perceived usefulness at a significance level of 0.001. In addition, perceived ease of use had a positive and significant effect on perceived usefulness and intention to use, and perceived usefulness had a positive and significant effect on intention to use at a significance level of 0.001. Nevertheless, the results showed that organizational support did not have a significant effect on perceived ease of use. Finally, there were significant indirect effects on the relationships among acceptance and use of technology, perceived ease of use, perceived usefulness, and intention to use. Implications –The findings present several implications for both academia and management practitioners, providing insights into crafting effective strategies to enhance users’ or employees’ technology adoption once new technologies and/or systems are introduced in the workplace. Originality/Value – This research sought to enhance comprehensive comprehension of the intricate interplay among the UTAUT Model, perceived ease of use, perceived usefulness, and intention to use, interpreting their collective influence on potential users’ decisions toward the use of systems or IT. Also, the research can fill existing gaps in the literature and provide valuable insights for refining technological capability and competencies, particularly focusing on international entrepreneurship.